Descriptive analysis of COVID-19 death at Patan Academy of Health Sciences - Shrestha, Ashis; Bajracharya, Sumana; Sharma, Rajiv; chhetri Budhathoki, Arpana (Journal of Patan Academy of Health Sciences, 2021)
Introduction: The Coronavirus Disease 2019 (COVID-19 ) pandemic has led to infection and deaths worldwide. The clinical and laboratory findings at presentation to emergency can provide clue for deaths. This study aims to analyze COVID-19 deaths, and clinical-laboratory findings at presentation. Method: This is a retrospective cross-sectional study conducted at Patan Hospital, Patan Academy of Health Science, Lalitpur, Nepal to analyze mortality due to COVID-19 during the year 2020. The study describes the clinical presentation, laboratory parameters at the time of presentation to the emergency department and clinical course during hospital stay. Result: Among 133 COVID-19 deaths analyzed, the median age was 61y (2d to 91y), males 73(54.9%), hypertension in 34(25.6%), 104(78.1%) had shortness of breath, 70(52.6%) fever and 34(25.6%) had cough on presentation. Median oxygen saturation on arrival was 77%, all 133(100%) required oxygen. Oxygen requirement at admission, ferritin (median 603 mcg/L), C- Reactive protein (median CRP 89.5 mg/) and lactate dehydrogenase (median LDH, 432 u/L) were not significantly correlated with duration of disease or hospital/ICU stay. Median duration of disease was 10d, hospital stay 8d and ICU stay 3d. COVID-19 deaths occurred due to respiratory failure in 105(78.9%). Conclusion: COVID-19 deaths were due to respiratory failure in 2/3rd (78.9% of 133), more in middle age (>46y) males with comorbidities, commonly hypertension. Abnormal vital signs, elevated CRP, ferritin, LDH, were seen in COVID-19 deaths. Oxygen requirement at admission was not correlated with duration of disease, or hospital/ICU stay.